2005
DOI: 10.1093/geronb/60.6.p320
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Cognitive Decline and Social Relations

Abstract: We assessed conjoint trajectories of cognitive decline and social relations over 7 years on a representative sample of community-dwelling elderly persons. We analyzed data using repeated measurement models. Social integration, family ties, and engagement with family were associated with cognitive function at advanced ages, controlling for education and introducing depressive symptoms, functional limitations, and chronic conditions as intervening variables. Association of social integration, through participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
148
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(173 citation statements)
references
References 40 publications
16
148
2
2
Order By: Relevance
“…19 A repeated-measures prospective longitudinal study of 964 community-dwelling adults aged over 65 years in Spain over 7 years found that the probability of cognitive decline was lower for older adults with a high frequency of visual contact with relatives, whereas contact with friends was protective against cognitive decline in women only. 17,38 An Australian study investigating the effect of social connections on memory scores up to 15 years later in 706 participants aged 65 years and over found that the rate of decline in the ability to recall personal life experiences was steeper for those with the smallest friend networks. 39 In other words, older adults in that study with the smallest number of social connections experienced the steepest decline in memory for life events with every passing year.…”
Section: Social Connectionsmentioning
confidence: 99%
“…19 A repeated-measures prospective longitudinal study of 964 community-dwelling adults aged over 65 years in Spain over 7 years found that the probability of cognitive decline was lower for older adults with a high frequency of visual contact with relatives, whereas contact with friends was protective against cognitive decline in women only. 17,38 An Australian study investigating the effect of social connections on memory scores up to 15 years later in 706 participants aged 65 years and over found that the rate of decline in the ability to recall personal life experiences was steeper for those with the smallest friend networks. 39 In other words, older adults in that study with the smallest number of social connections experienced the steepest decline in memory for life events with every passing year.…”
Section: Social Connectionsmentioning
confidence: 99%
“…6 Longitudinal studies show that larger social networks, 7,8 access to social resources, 9,10 and community engagement reduce dementia diagnoses. [11][12][13][14][15][16][17] Hypotheses on mechanisms by which social relationships can reduce cognitive decline include: delay of cognitive atrophy (Buse it or lose it^), 18 higher cognitive reserve, 19 and preventing stress-related cognitive declines. 6 This is likely a bidirectional relationship, where cognitive decline can lead to altered social relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Inability to utilize social resources may indicate a barrier to independent living. For social engagement, one might expect decreased community involvement at lower cognitive status, 10,12,13 but less is known regarding social isolation at home. Less interaction with friends, family and the community is often the most noticeable social sign of cognitive impairment, and a better characterization of such differences could provide clues on when to screen for cognitive loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, contribuiria com a melhora das relações com os cuidadores, por meio da realização conjunta de atividades significativas que promovessem a busca e a preservação do senso de identidade. Não há consenso sobre quais atividades seriam, isoladamente, favorecedoras de estimulação cognitiva, devido à influência de alta subjetividade, variabilidade cultural e por serem gênero-específicas (Reuben et al, 1990 Apesar das diferentes classificações encontradas na literatura, a somatória do número de atividades complexas realizadas mostrou-se associada aos melhores níveis de função cognitiva e diminuição do risco de declínio cognitivo (Aartsen et al, 2002;Bassuk et al, 1999;Di Rienzo, 2009;Foubert-Samier et al, 2012;Gallucci et al, 2009;Glei et al, 2005;Iwasa et al, 2012;Li et al, 2013;Scarmeas et al, 2001;Sobral & Paúl, 2013;Zunzunegui et al, 2005). Os resultados desse estudo corroboram com os anteriores, onde a realização de um maior número de atividades diminuiu a incidência de declínio cognitivo, mesmo após ajuste pelas demais covariáveis e, principalmente, pela escolaridade.…”
Section: Discussionunclassified